Cost analysis of using hybrid microwave post-sintered aluminium oxide inserts - Ariff, Tasnim Firdaus; Azmi, Muhammad Firdaus; Iqbal, Mohammad (PAK publishing group, 2014)
This research investigates the effect of heat treatment using hybrid microwave energy toward the enhancement of tool life in Aluminium Oxide (Al₂O₃) inserts. Al2O3 tool insert is known for its attractive properties including high fracture toughness, strength and wear resistance at elevated temperatures. Heat treatment was performed on these inserts by post-sintering them for 15 minutes at 600°C using conventional heating and hybrid microwave energy. Dry machining was performed on T6061 Aluminium alloy and AISI 01 Cold Worked Steel for tool life analysis at three different cutting speeds; 245, 305 and 381 m/min. Tool life for Al2O3 had increased by 87.5-92% and 22.7-70% for T6061 Aluminium alloy and AISI 01 Cold Worked Steel respectively. Cost analysis was performed on these post-sintered Al2O3 inserts and found that there are economical benefits in the tooling cost when compared with the untreated Al2O3 inserts.